Forage management intensification and supplementation strategy: Intake and metabolic parameters on beef cattle production - Delevatti, Lutti Maneck [UNESP]; Romanzini, Eliéder Prates [UNESP]; Koscheck, Jefferson Fabiano Werner; da Ross de Araujo, Tiago Luis [UNESP]; Renesto, Diego Monteira [UNESP]; Ferrari, Adriana Cristina [UNESP]; Barbero, Rondineli Pavezzi; Mulliniks, John Travis; Reis, Ricardo Andrade [UNESP] (Elsevier, 2019)
Improving animal performance on pasture requires grazing management that optimizes forage intake in combination with the appropriate supplementation strategy. The objective was to determine the effects of sward canopy height and level of supplementation on forage intake, digestibility, and ruminal fermentation kinetics of Nellore steers in a double Latin square design with repeated measures. Treatments were three sward heights with differing levels of supplementation and included: (1) short height with high supplementation (SH-HS, 15 cm and 0.6% BW); (2) short height with moderate supplementation (SH-MS, 15 cm and 0.3% BW); (3) moderate height with moderate supplementation (MH-MS, 25 cm and 0.3% BW); (4) moderate height with low supplementation (MH-LS, 25 cm and 0.1% BW); (5) tall height with low supplementation (TH-LS, 35 cm and 0.1% BW); and (6) tall height with no supplementation (TH-WS, 35 cm). Intake of crude protein and total digestible nutrients was greater (P < 0.05) with tall swards and moderate supplementation rates. Nutrient digestibility among treatments did not differ (P ≥ 0.21), possibly due to the availability of high-quality forage during the wet season. Likewise, rate of neutral detergent fiber degradability did not differ (P ≥ 0.19) among treatments. Ruminal ammonia nitrogen differed (P = 0.02) among treatments with moderate supplementation having the greatest (SH-MS) and lowest (MH-MS) concentrations (13.6 and 9.7 mg/dL, respectively). Ruminal pH and volatile fatty acid concentrations did not differ (P ≥ 0.18) among treatments. Microbial N flow to the small intestine and efficiency of microbial synthesis exhibited a quadratic response with moderate sward height treatments having greater values. With these treatments and under the conditions of this study, various combinations of sward height and supplementation level did not alter rumen fermentation kinetics.
Keywords: Grazing management; Nutritional evaluation; Tropical pastures